The Impact of Fintech on Traditional Financial Banking in West Africa - Boubacar Emine Dahi, Mohamed (International Journal of Scientific Research and Management (IJSRM), 2024)
Fintech, the convergence of finance and technology, has emerged as a transformative force reshaping the global financial landscape. While its influence is evident across the world, its impact on traditional financial systems in less developed countries remains a subject of exploration and analysis. This paper aims to investigate the multifaceted effects of fintech on traditional financial systems in less developed countries, examining both the opportunities and challenges it presents. Through an examination of various case studies and empirical evidence, this paper seeks to provide insights into the evolving dynamics of financial inclusion, innovation, regulation, and economic growth spurred by fintech in less developed countries.